2015
DOI: 10.7554/elife.08077
|View full text |Cite
|
Sign up to set email alerts
|

TALPID3 controls centrosome and cell polarity and the human ortholog KIAA0586 is mutated in Joubert syndrome (JBTS23)

Abstract: Joubert syndrome (JBTS) is a severe recessive neurodevelopmental ciliopathy which can affect several organ systems. Mutations in known JBTS genes account for approximately half of the cases. By homozygosity mapping and whole-exome sequencing, we identified a novel locus, JBTS23, with a homozygous splice site mutation in KIAA0586 (alias TALPID3), a known lethal ciliopathy locus in model organisms. Truncating KIAA0586 mutations were identified in two additional patients with JBTS. One mutation, c.428delG (p.Arg1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 61 publications
(126 reference statements)
1
57
0
Order By: Relevance
“…Despite the situs of the viscera and turning/patterning of the heart tube being normal (Stephen et al, 2014), the anatomy of the ta 3 body is severely dysmorphic. The ta 3 body axis is shortened (Stephen et al, 2015), the lungs are hypoplastic and the liver is fibrotic and cholestatic (Davey et al, 2014). Skeletogenesis is aberrant (Macrae et al, 2010), embryos exhibit unusual vascular abnormalities (Davey et al, 2007) and development and differentiation of the central nervous system is impaired (Buxton et al, 2004; Stephen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the situs of the viscera and turning/patterning of the heart tube being normal (Stephen et al, 2014), the anatomy of the ta 3 body is severely dysmorphic. The ta 3 body axis is shortened (Stephen et al, 2015), the lungs are hypoplastic and the liver is fibrotic and cholestatic (Davey et al, 2014). Skeletogenesis is aberrant (Macrae et al, 2010), embryos exhibit unusual vascular abnormalities (Davey et al, 2007) and development and differentiation of the central nervous system is impaired (Buxton et al, 2004; Stephen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The KIAA0586 protein, eventually named TALPID3, was isolated in an early centrosomal proteome analysis (Andersen et al, 2003) and was confirmed to be a centrosomal protein (Yin et al, 2009) that normally localized in a ring at the distal end of the basal body (Kobayashi et al, 2014). The TALPID3 protein was shown to be required for docking of the basal body to the cell surface (Yin et al, 2009) prior to ciliogenesis (Kobayashi et al, 2014) and has also been implicated in centrosome migration (Stephen et al, 2013), control of centrosome length (Stephen et al, 2015) and formation of centriolar satellites (Kobayashi et al, 2014). Loss of the TALPID3 protein, in various model species, resulted in a loss of cilia (Bangs et al, 2011; Ben et al, 2011; Yin et al, 2009), both non-motile and motile (Stephen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Homozygous occurrence of this variant in healthy individuals was assumed to ‘either be due to protective modifiers or a low mutational load in the ciliome of the respective person’ 6. Based on the frequency data of 0.003117 for the c.428delG variant obtained from the gnomAD database—which also includes two homozygous carriers—we conclude that the c.428delG variant likely represents a mild hypofunctional allele, which is not disease causing in a homozygous situation.…”
Section: Discussionmentioning
confidence: 97%
“…The putative conflicting observation of homozygosity of the KIAA0586 c.428delG variant in both, patients with JBTS and healthy individuals, was discussed previously 6. Homozygous occurrence of this variant in healthy individuals was assumed to ‘either be due to protective modifiers or a low mutational load in the ciliome of the respective person’ 6.…”
Section: Discussionmentioning
confidence: 99%